High‐Performance Liquid Chromatographic Resolution of Neutral and Cationic Hetero[6]Helicenes. Issue 4 (22nd February 2016) - Labrador, Geraldine M.; Bosson, Johann; Breitbach, Zachary S.; Lim, Yeeun; Francotte, Eric R.; Sabia, Rocchina; Villani, Claudio; Armstrong, Daniel W.; Lacour, Jérôme
Abstract: Cationic hetero[6]helicenes1 +, 2 + and3 + have been recently disclosed. Herein we report on their enantiomeric separation using high‐performanceliquid chromatography . Separation of the antipodes can be achieved in preparative scale on neutral adducts with Chiralcel OD‐I or Chiralpak ID CSP. Selectivity factors of 1.90, 1.67, and 1.96 were obtained for1-H, 2-H, and3-H, respectively. Separation can also be performed on the carbenium ions on regular Chiralpak IA CSP using water‐containing eluents, thus allowing for enantiomeric purity determinations in aqueous environments. Resolution of neutral and cationic helicenes is also achieved on more recently developed LARIHC columns. The versatility of the cyclofructan phases allows for baseline separations for both cases and their loading capabilities are demonstrated. Finally, the configurational stability of1 +, 2 +, and3 + was measured. For each replacement of an oxygen atom by an amino group, theracemization barrier increases significantly (Δ G ‡  = 29.8, 36.3 and >37 kcal mol ‐1 for1 +, 2 +, and3 + respectively). Chirality 28:282–289, 2016 . © 2016 Wiley Periodicals, Inc. Abstract :